La influencia del Papado de Aviñón sobre la música medieval española : la aparición del estilo ars subtilior - Pajor, Enikő (Acta Hispanica, 2012)
I am not a musicologist but for more than twenty years I have been regularly cultivatingGregorian chant. In the same way, personally I feel very close to medieval music. Preparing atraining course for librarians specialised in music, Ifound a style called "Ars Subtilior" which isgenerally little known even among musiáans, as it only lasted a few decades in the Middle Agesin France, Spain and Italy. I consider it important to provide some historical and theoretical dataneeded to understand the importance of this revolutionary new style in its historical context.